The long-term impacts of breastfeeding on educational attainment of adults - Andrew Hussey (Review of Economics of the Household, 2025)
Using data from the National Longitudinal Study of Adolescent Health, we examine the impact of breastfeeding on the likelihood of obtaining a college degree and attending graduate school. Using a doubly robust estimation technique, we find that having been breastfed is linked to an increased probability of obtaining a college degree, but its association with graduate school attendance is largely insignificant. The effect on college degree attainment is primarily concentrated among males, blacks, and whites. Investigating potential mechanisms, we find evidence that part of these effects is operating through the impact of breastfeeding on adolescents' cognitive ability.
Keywords: I12; I23; J15; I18; C21; 330; Breastfeeding; Educational attainment; Human capital; Doubly robust estimation; College degree; Graduate school attendance